Multimodal Diagnosis of Right Ventricular Hamartoma - V. S. Bereznitskiy; S. A. Alexandrova (Вестник рентгенологии и радиологии)
Primary cardiac tumors occur quite rarely, while the symptoms in patients with this pathology are very nonspecific. The data of physical examination and the results of electrocardiography and radiography are often less informative. In this connection, modern high-tech medical imaging tools play a very important role in the identification and differential diagnosis of this category of space-occupying lesions. The paper describes a case of right ventricular hamartoma diagnosedd in an adult patient with the long-term asymptomatic course of the disease.